Experimental study of the disinfection performance of low concentration gas chlorine dioxide from the simulated dishwasher cabinet on tableware - Yanzhen Han; Peiyong Ning; Yongfan Li; Baiqi Wang; Yang Liu; Ying Wang; Peng Zhang; Yongmei Zhang; Yuan Wang; Xin Gao; Xiaoqing Fan; Xiaoyan Li (Applied Food Research)
The ability of dishwashers to remove pathogens holds significant practical value. To evaluate the disinfection effect of a low-concentration chlorine dioxide gas in a simulated dishwasher cabinet, this study provides a meaningful foundation and support for the development of modern dishwashers with enhanced disinfection capabilities. Carrier quantitative germicidal test and field disinfection test of object surface were conducted to study the germicidal effect of the dishwasher on Staphylococcus aureus, Escherichia coli and Salmonella on stainless steel carriers. Additionally, simulated metals corrosion test were also conducted within the dishwasher cabinet. The results indicate that under operational conditions of 20 °C–25 °C and relative humidity 80 %–90 %, run the disinfection module for 30 min, then turn it off to stop gas release and maintains in this state for 15 min, the killing logarithm values of Staphylococcus aureus, E. coli and Salmonella on the carriers were all above 3.00. In the field disinfection test, stainless steel food trays normally washed without disinfection were placed in the simulated dishwasher cabinet and proceed a disinfection procedure, and the three bacteria were not detected. In the metals corrosion test, chlorine dioxide gas was found to be essentially non-corrosive to stainless steel, copper, and aluminum, while it caused mild corrosion to carbon steel. This study conformed the performance of the simulated dishwashers in removing pathogens through the disinfection program utilizing low concentration chlorine dioxide gas.